Ulva lactuca methanolic extract improves oxidative stress-related male infertility induced in experimental animals. (3rd September 2021) - Ghareeb, Doaa A.; Abd-Elgwad, Alshimaa; El-Guindy, Nihal; Yacout, Galila; Zaatout, Hala H.
Abstract: Aim: This study designated to investigate and compare the therapeutic effect of Ulva lactuca methanolic extract against oxidative stress (OS)-infertility induced by naturally occurring prooxidants (gossypol) and selenium- vitamins A, C, and E (selenium-ACE) drug. Methods: Male infertility was induced in rat by intraperitoneal injection of 5 mg/kg gossypol eight times then the treatment was carried out with 100 mg/kg ulva methanolic extract oral administration for one or two weeks, after this period OS, and male infertile markers were detected in blood and/or testes. Results: Gossypol stimulated male infertility by increasing testicular OS markers and decreasing semen quality, hyaluronidase enzyme activity, and blood testosterone level. The treatment with ulva methanolic extract improved gossypol related adverse effects. The treatment period for two weeks with extract was the most potent one. Conclusions: Ulva methanolic extract could be considered as good antioxidant therapeutic candidate for OS linked male infertility.